2018
DOI: 10.15570/actaapa.2018.18
|View full text |Cite
|
Sign up to set email alerts
|

Store-and-forward teledermatology for the most common skin neoplasms in Ukraine

Abstract: Introduction: Among all malignancies in Ukraine in 2016, the group of non-melanoma skin cancers headed the list in men and made up 21.6%. This group was second in women and made up 17.6%. The diagnostics of skin tumors are becoming increasingly relevant. Methods: The store-and-forward (SAF) method was used. The study included patients that were remotely diagnosed with melanocytic nevi, seborrheic keratoses, skin cancer, and skin melanoma. Patients signed up for remote diagnostics, were examined in person by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Temiz et al (2020) were the first to propose that teledermatology could serve as a suitable method for the reduction of FTF consultations during the pandemic [ 39 ]. When teledermatology was used prior to the pandemic, photographs were most commonly taken by healthcare professionals using a digital camera or mobile phone [ 40 , 41 , 42 , 43 ]. There are just a few publications in the literature of the use of store-and-forward teledermatology consultations where photos were provided by the patients with a mobile phone’s camera and application [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Temiz et al (2020) were the first to propose that teledermatology could serve as a suitable method for the reduction of FTF consultations during the pandemic [ 39 ]. When teledermatology was used prior to the pandemic, photographs were most commonly taken by healthcare professionals using a digital camera or mobile phone [ 40 , 41 , 42 , 43 ]. There are just a few publications in the literature of the use of store-and-forward teledermatology consultations where photos were provided by the patients with a mobile phone’s camera and application [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…An ongoing study in Australia is examining the use of 3D-TBP in an integrated telemedicine network of 15 systems in urban, regional, and remote areas [34]. Among patients with melanoma, outcomes have been found to be poorer in rural regions than in urban regions [16,[35][36][37]. Some earlier studies have shown that although patients have concerns regarding privacy, most patients would share identifiable images for their own personal medical record [7,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Among patients with high risk for melanoma, Moye et al [11] found that monitoring with TBP led to decrease in anxiety. Kravets et al [36] reported similar diagnostic accuracy with teledermatological examination versus clinical examination and teledermoscopy versus dermoscopy [36, 37]. Common problems with conventional images sent to teledermatology consultations are poor image quality and wrong focus.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be a paucity of published evidence of TD usage from Eastern European countries although no doubt there has been a degree of uptake for the same reasons as elsewhere [ 72 ]. In Russia, with a state-run health care insurance which is without charge, Alexey Sergeev, Professor, Sechenov University, Moscow Russia, states that “thousands of us consult online for free and for reward” through TD.…”
Section: Methodsmentioning
confidence: 99%